Pengembangan E-LKPD Jelajah Lereng Gunung Api Berbasis Deep Learning untuk Mendukung Literasi Lingkungan - Dwi Febby Mustika Ningrum; Suroso Mukti Leksono; Mudmainah Vitasari (Universitas Cokroaminoto Palopo, 2026)
This research is based on the increasing global environmental crisis, which is exacerbated by the low level of environmental literacy among students in Indonesia, a condition that is the reason for the development of contextual science learning materials oriented towards an in-depth learning approach. Accordingly, this study aims to develop an Electronic Student Worksheet (e-LKPD) entitled